The effect of private tutoring on performance in mathematics in Turkey: A comparison across occupational types - Unal, Hasan; Ozkan, E. Mehmet; Milton, Sande; Price, Kacey; Curva, Fely (ELSEVIER SCIENCE BV, 2010)
In Turkey, while overall involvement in public education has increased significantly, there still remain important inequalities between social groups in academic achievement and admission to higher education. This study estimates the effect of private tutoring (dersane) in Turkey in 15-year-old students with parents in four occupational categories. Analyzing PISA (2006) data, we found that the effect of private tutoring in math was relatively strong for all four occupational strata: one hour of tutoring is worth between 12 and 15 points on the math achievement test, and this return to investment is constant across types. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: International education; Educational policy; Tutoring; Equality; PISA; Education & Educational Research